An overiew of non medical prescribing across one strategic health authority: a questionnaire survey - Courtenay Molly; Carey Nicola; Stenner Karen (BMC, 2012)
Abstract Background Over 50,000 non-medical healthcare professionals across the United Kingdom now have prescribing capabilities. However, there is no evidence available with regards to the extent to which non-medical prescribing (NMP) has been implemented within organisations across a strategic health authority (SHA). The aim of the study was to provide an overview of NMP across one SHA. Methods NMP leads across one SHA were asked to supply the email addresses of NMPs within their organisation. One thousand five hundred and eighty five NMPs were contacted and invited to complete an on-line descriptive questionnaire survey, 883 (55.7%) participants responded. Data was collected between November 2010 and February 2011. Results The majority of NMPs were based in primary care and worked in a team of 2 or more. Nurse independent supplementary prescribers were the largest group (590 or 68.6%) compared to community practitioner prescribers (198 or 22.4%), pharmacist independent supplementary prescribers (35 or 4%), and allied health professionals and optometrist independent and/or supplementary prescribers (8 or 0.9%). Nearly all (over 90%) of nurse independent supplementary prescribers prescribed medicines. Approximately a third of pharmacist independent supplementary prescribers, allied health professionals, and community practitioner prescribers did not prescribe. Clinical governance procedures were largely in place, although fewer procedures were reported by community practitioner prescribers. General practice nurses prescribed the most items. Factors affecting prescribing practice were: employer, the level of experience prior to becoming a non-medical prescriber, existence of governance procedures and support for the prescribing role (p < 0.001). Conclusion NMP in this strategic health authority reflects national development of this relatively new role in that the majority of non-medical prescribers were nurses based in primary care, with fewer pharmacist and allied health professional prescribers. This workforce is contributing to medicines management activities in a range of care settings. If non-medical prescibers are to maximise their contribution, robust governance and support from healthcare organisations is essential. The continued use of supplementary prescribing is questionable if maximum efficiency is sought. These are important points that need to be considered by those responsible for developing non-medical prescribing in the United Kingdom and other countries around the world.